Bridger Trail [large type] - Rundell, B. N. (Rundell, B. N. McCain chronicles, 2026)
"Elijah McCain faces his most formidable challenge yet. Having spent the last few years alone with most of his time expended in war, rising to the rank of Lieutenant Colonel in the Union Cavalry, losing his wife, and traveling cross-country in search of his twin sons, McCain has had little time for himself-or to spend with others. When he and his friend, Charlie Two Toes, decide to lead a wagon train north into the goldfields of Montana Territory, the dangers they meet are far more than they bargained for, including the unexpected appearance of a beautiful native Shoshone woman who instills in McCain a newfound sense of hope. Navigating five hundred miles through hostile lands, McCain begins to wonder: can he make it to Bridger Trail in one piece-or is he finally at the end of his rope?"--